1981
DOI: 10.1177/29.3.481
|View full text |Cite
|
Sign up to set email alerts
|

Proteinases in pathology. Usefulness of histochemical methods

Abstract: The usefulness of optimized and newly elaborated histochemical methods for proteinases is illustrated on two selected substances. DAP IV (Gly-Pro-MNA,FBB,pH 7.2) was discovered in 39% and DAP II (Lys-Ala-MNA,FBB,pH 5.5) in 60% of the lymphocytes of human peripheral blood (ly). The reaction product of such ly differs in quality and quantity. On the ultrastructural level, the reaction product of DAP IV (Gly-Pro-MNA,HNF) was found in cell membranes and lysosomes. Enzyme activity in other areas was probably suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
2

Year Published

1983
1983
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(17 citation statements)
references
References 46 publications
2
13
0
2
Order By: Relevance
“…Svenson et al (23) purified DPP IV from pig small intestinal brush border membrane. DPP IV activity has also been localized in situ on the brush border of enterocytes of the small intestines of some animals, including humans, by the use of histochemical methods (2,3,8). In the present study, it was revealed that DPP IV in the rat small intestine was restricted to the external surface of brush border membranes in the enterocytes, thus confirming previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…Svenson et al (23) purified DPP IV from pig small intestinal brush border membrane. DPP IV activity has also been localized in situ on the brush border of enterocytes of the small intestines of some animals, including humans, by the use of histochemical methods (2,3,8). In the present study, it was revealed that DPP IV in the rat small intestine was restricted to the external surface of brush border membranes in the enterocytes, thus confirming previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…Our results were in agreement with those of previous studies (2,3,5,7,9,10,16), and confirmed the evidence that DPP IV is a brush border membrane peptidase. Furthermore, using a pre-embedding peroxidase labeled antibody (Fab' fragments) technique, we were able to more precisely determine the subcellular localization of DPP IV in these organs.…”
Section: Discussionsupporting
confidence: 93%
“…The second explanation may be the fact that the tonsils and peripheral blood of children have a greater number of activated lymphocytes than those of adults, especially CD4 ϩ and (16,18), which may be a source of the serum form of DPP IV. Indeed, Lojda (17) demonstrated that DPP IV activity occurs in 39% of peripheral blood lymphocytes and exclusively in T lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The enzymohistochemical determination of DPP IV activity in tonsillar tissue was performed according to the method of Lojda (17). Briefly, 4 mg of Gly-Pro-4-methoxy-␤-naphthylamide (Sigma, Germany) was dissolved in 500 l of N,N-dimethylformamide (ICN, OH).…”
Section: Methodsmentioning
confidence: 99%